The Effect of Exchange Value and Inflation on Non-Oil and Gas Export Value Period 2015 – 2021 - Albinia, Sava; Sofyan, Mohammad (Yayasan Sinergi Kawula Muda, 2023)
This study aims to analyze the effect of Exchange Rates and Inflation on the Value of Non-Oil and Gas Exports. The independent variables used in this research are the Exchange and Inflation rates. The dependent variable used is the value of Indonesia's Non-Oil and Gas Exports. Data collection uses secondary data obtained from Badan Pusat Statistik and Bank Indonesia period 2015-2021, the data is analyzed using multiple linear regression analysis which is processed using the Eviews program version 12. The results of this study indicate that the variables Exchange Rate and Inflation affect Export Value Non-Oil and Gas. The Exchange Rate does not affect the Non-Oil and Gas Exports Value. The Inflation Rate affects the Value of Non-Oil and Gas Exports.